The Great Bell Tower of Kyiv Caves Lavra as a spatial landmark in works of the Orthodox travellers (the 19th – early 20th c.) - Kizlova, A. (Сiверянський літопис, 2025)
The purpose of the publication is to examine mentions of the Great Bell Tower in works by Orthodox visitors to Kyiv, focusing on their reactions upon seeing it from afar. By analyzing these accounts, we can gain insight into the bell tower’s significance as a landmark and its impact on visitors’ perceptions of Kyiv. Methods. It was taken into account that publications issued within the Russian Empire were subject to censorship, so authors and editorial boards had to adapt to this. This research adheres to principles of historical authenticity and impartiality, objectivity and historicism, employing a range of analytical approaches. To establish the historical context, the study utilizes methods of source discovery and evaluation, comparative historical analysis, and synthesis of information. These techniques allow for a comprehensive examination of the subject matter within its broader historical framework. Scientific novelty. This article is the first to comprehensively examine the works of Orthodox travelers who mentioned their distant sightings of the Great Lavra Bell Tower. Conclusions. When combining reports from different periods and diverse viewpoints – clergy, laypeople, local travellers, and visitors from other provinces – collectively, they evoke the essence of the Lavra bell tower. Descriptions primarily feature elements visible from a distance: its prominence against Kyivʼs skyline and the scenic view of its golden dome. They then shift to the spiritual aspect that motivates pilgrims, and the architectural design of its towers, noting both height and shape. Many accounts mention spotting the tower from considerable distances, such as 37–42 km west of the Dnipro river or 48 km away from a train. Sources describe the emotional impact on people first glimpsing the brilliant golden domes and crosses radiating in sunlight from afar. Examples include individuals leaning towards the tower in reverence or praying softly as they passed nearby. The tower was a constant presence, visible both upon arrival to and departure from Kyiv. It served as a connection between the city and travellers, becoming an unparalleled ornament and symbol of Kyiv. Visitors and pilgrims alike admired its tall, slender form and the radiance of its domes. The image of the Kyiv Caves Lavra became inextricably linked with its magnificent bell tower, which itself was an astonishing sight due to its height, massiveness, and incredible design. Seeking out the Lavra bell tower became a custom for religious people and a point of interest for travellers. These powerful yet often straightforward descriptions from various observers brought the tower to life. The Kyiv Lavra bell tower evolved into a remarkable emblem of the city’s spiritual and historical leadership, a ceremonial beacon for those seeking sanctification, and a constant source of attraction and wonder for all who knew of it. It is possible to argue that the Great Bell Tower was not only an architectural and spatial, but also a spiritual landmark for visitors to Kyiv.